Prediksi Peluang Penjualan Liquid Vape Di Area Lingkungan Kampus Universitas Pelita Bangsa - Agus Purwanto; Aldi Kirana (Prosiding Sains dan Teknologi, 2022)
The decision tree method is a method that converts very large facts into a decision tree that presents rules. The decision tree method is useful for exploring data, as well as finding hidden relationships between a number of potential input variables and target variables. The decision tree of the C4.5 algorithm is built with several steps including selecting the attribute as the root, creating a branch for each value and dividing the cases into branches. The problem that occurs is that there are no Liquid Vape sellers in the Pelita Bangsa University environment, which often makes it difficult for vape user students when they run out of Liquid Vape in the campus environment. Even though at this time the vape trend is getting more and more demand, there are quite a lot of consumers looking for Liquid Vape. This study aims to analyze the sales opportunities of Liquid Vape in the Pelita Bangsa University environment. The population used in this study were several students of Pelita Bangsa University. Sampling The technique used is through a questionnaire. The sampling criteria were 43 students. The data collection method in this study used a questionnaire. The accuracy results obtained from this study were 81.9%. Keywords: Vape, Liquid Vape, Vape User, Opportunity